Emission Taxes and Product Differentiation in the Presence of Foreign Firms. - Gautier, Luis (Wiley, 2016)
Industries characterized by differentiated products are important contributors of greenhouse gases and currently subject to market-based policies such as emission taxes. In the context of developing countries, fears about foreign investment leaving the country are often used as an argument not to address industry emissions through emission taxes. This paper develops a Cournot model with product differentiation in the presence of abatement efforts where host and foreign firms are subject to an emission tax. The analysis indicates that abatement efforts and differences in pollution intensity coefficients across firms may play a significant role in the characterization of optimal policy. The analysis also suggests that the government may opt to encourage foreign, less pollution-intensive firms via higher taxation. Additionally, this paper examines how an optimal emission tax may be adjusted as products become more differentiated; industry emissions may fall/rise as a result of more differentiated products. One important contribution of this paper is that it emphasizes the role of abatement efforts, product differentiation, and differences in pollution intensity coefficients across firms in the characterization of the optimal emission tax.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/15154?template=romeo
Keywords: Diferenciación del producto; Impuestos ambientales; Oligopolios; Environmental taxes; Free entry; Oligopoly; Horizontal product differentiation